Ireland : Financial Sector Assessment Program-Technical Note on Financial Safety Nets and Crisis Management. (IMF Staff Country Reports; Country Report, 2022)
This Note assesses the bank recovery, resolution, and crisis preparedness regime in Ireland. It analyzes laws, policies, procedures, institutional capacity and coordination arrangements for bank failure resolution and for managing financial distress and crises. The assessment is focused on banks under the direct remit of the Central Bank of Ireland and does not evaluate the role played by the European Central Bank and the Single Resolution Board for Ireland's largest banks. The Note also assesses steps toward adopting a recovery and resolution regime for insurers. The Note is guided by international standards, in particular the Key Attributes of Effective Resolution Regimes for Financial Institutions promulgated by the Financial Stability Board.